2021
DOI: 10.3389/fphar.2020.609522
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Study Comparing the Tolerance, Immunogenicity, and Pharmacokinetics of Proposed Biosimilar BAT1806 and Reference Tocilizumab in Healthy Chinese Men

Abstract: Objective: The study aimed to explore the bioequivalence of a proposed biosimilar BAT1806 to its reference products marketed in the EU and US (RoActemra-EU and Actemra-US) among healthy Chinese men. The tolerance, immunogenicity, and pharmacokinetics (PK) of the three drugs were also investigated.Methods: In this randomized, double-blind, single-dose, three-arm, parallel study, a single-dose of 4 mg/kg of the reference products, or the biosimilar was administered to the participants. The participants were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
1
5
1
Order By: Relevance
“…A total of 4 (10.00%) and 3 (8.11%) subjects tested positive for treatment-induced ADA throughout the study for the test and reference groups, respectively. The total rate of ADA positivity in the present study was lower than that reported in other tocilizumab biosimilar studies, [13][14][15] on account of the different immunogenicity assessment period (28 days vs. 48 or 57 days). Due to the limited number of ADA-positive subjects, subgroup analysis of bioequivalence and safety for ADA-positive subjects was not feasible, thus the effect of the immunogenic responses on PK and safety could not be assessed.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…A total of 4 (10.00%) and 3 (8.11%) subjects tested positive for treatment-induced ADA throughout the study for the test and reference groups, respectively. The total rate of ADA positivity in the present study was lower than that reported in other tocilizumab biosimilar studies, [13][14][15] on account of the different immunogenicity assessment period (28 days vs. 48 or 57 days). Due to the limited number of ADA-positive subjects, subgroup analysis of bioequivalence and safety for ADA-positive subjects was not feasible, thus the effect of the immunogenic responses on PK and safety could not be assessed.…”
Section: Discussioncontrasting
confidence: 89%
“…PK parameters generated from the present study were compared with those reported in the literature (Table 4). 13,15 The study dosage was 4 mg/kg in both the present study and literature 1 13 ; however, it was 8 mg/kg in literature 2. 15 AUC 0– t , AUC 0–∞ , and C max in the present study were slightly lower than the equivalent parameters reported in literature 1, which may be attributed to the different metabolic characteristics of the study population, or the different detection methods used for tocilizumab.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…High mannose glycans have the potential to change the PK of a protein (i.e., by increasing the rate of drug clearance), therefore, having lower amounts of high mannose in the biosimilar could increase the relative half-life of the product. However, the quantitative change we observed was small (in the order of 1–2%) and no meaningful impact was anticipated, which was confirmed by non-clinical and clinical studies that demonstrated equivalent PK of BAT1806/BIIB800 in a comparative PK study [ 12 ], and similar trough serum concentrations in a phase III trial in patients with RA [ 13 ]. Therefore, differences observed in high mannose content can be considered clinically non-meaningful.…”
Section: Discussionsupporting
confidence: 57%
“…Clinical similarity of BAT1806/BIIB800 compared with TCZ was demonstrated in published phase I and III studies [ 12 , 13 ]. Here we present the physicochemical, structural and biological characterization of BAT1806/BIIB800 using a comprehensive comparability exercise applying a multitude of analytical techniques and in vitro assays to determine its similarity with China-, EU- and US-sourced TCZ.…”
Section: Introductionmentioning
confidence: 97%